Outcome of external cephalic version (ECV) in singleton pregnancy with uncomplicated breech presentation at term in a tertiary rural hospital - Vedpathak, Sachin G.; Nayak, Vaishali R. Korde; P., Panigrahi P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Breech presentation is the most common malpresentation. The incidence of breech presentation at term is 3-4%. Objective of present study was to evaluate the outcome of external cephalic version (ECV) in singleton pregnancy with uncomplicated breech presentation at term in tertiary rural hospital and to analyze the immediate and ultimate outcome of external cephalic version done in term pregnancy with breech presentation with gestational age ≥37 weeks. Methods: This study was conducted at MIMER Medical college and BSTR Hospital, Talegaon Dabhade. Patients with breech presentation at term were studied over duration of 2½ years. 50 patients with breech presentation ≥37 weeks fulfilling the inclusion criteria underwent External cephalic version (ECV). Further obstetric progress is studied with the perinatal outcome and results were analyzed. Results: ECV was successful in 66% cases, out of which 88% cases had vaginal delivery and 12 % cases had LSCS for obstetric indication. Perinatal outcome was not affected with ECV. Conclusions: ECV at term significantly reduces both the incidence of breech delivery and caesarean section rate for breech delivery. ECV does not adversely affect the maternal and perinatal outcome.